If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + -2x = 7x + 23 Reorder the terms: 48 + -2x = 23 + 7x Solving 48 + -2x = 23 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 48 + -2x + -7x = 23 + 7x + -7x Combine like terms: -2x + -7x = -9x 48 + -9x = 23 + 7x + -7x Combine like terms: 7x + -7x = 0 48 + -9x = 23 + 0 48 + -9x = 23 Add '-48' to each side of the equation. 48 + -48 + -9x = 23 + -48 Combine like terms: 48 + -48 = 0 0 + -9x = 23 + -48 -9x = 23 + -48 Combine like terms: 23 + -48 = -25 -9x = -25 Divide each side by '-9'. x = 2.777777778 Simplifying x = 2.777777778
| 5-(4-a)=2a | | -14n+16=-12n-16 | | 5x-7=3x+15 | | 140-5x=31+16 | | 3(q+4)+4q+1= | | 7(2v+1)-3(9v+2)=40 | | -9=517n | | 3-2(x-2)=10 | | 8-7x=178-42x | | x+8000=70006 | | 8x+23-4=36 | | 4x+21=14x-29 | | x+8000=7000642 | | 4x+8=38 | | x-12=5x-4 | | 3t-5=7+9t | | 4(5t+3)=24 | | 2x+4/3=8 | | 2x+4/4=8 | | 3(6+c)=2(c-5) | | x^2(x^7)(x^11)= | | 7-5x=4x-11 | | 9(6c-1)-14=52c+9 | | 9(3x+6)=(x-2) | | 52x^2+5x-100=0 | | 5(y-2)=2y-31 | | 20(c+-50)=19000 | | 2-5x=18+3x | | 9x+8=7x+36 | | (10)=2x-6 | | x=3x+16 | | 3y=48+18ty |